Madu Banyu Asin: Market Penetration Strategy For Vannamei Shrimp Business In Kebumen - Mayang Wahyu Buana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to analyse Madu Banyu Asin's business performance in terms of production, human resources, and finance; to evaluate the effectiveness of market penetration strategies on sales growth; and to assess the effectiveness of social media marketing in increasing brand awareness and consumer brand engagement. The company's performance has improved over the last three months as a result of the deployment of partial harvesting, a planned organisational structure, and financial recovery from losses. In terms of human resources, a well-planned organisational structure aids team effectiveness. In terms of finance, the company generates profits that consistently increase every month. The market penetration strategy has successfully increased sales and expanded the B2B partner network. In addition, the market penetration strategy enhances the company's competitiveness in the B2B segment. The social media marketing strategy implemented has successfully enhanced brand awareness and consumer brand engagement through interactions on Instagram and WhatsApp Business, building long-term relationships. In terms of production, there has been a commitment to quality and sustainability. This study concludes that the implementation of integration between market penetration strategy and social media marketing strategy effectively enhances business performance, successfully expands the B2B partner network, and sustainably strengthens brand positioning.